TEKHNOLOGI PEMBELAJARAN (DEMONSTRASIONAL) UNTUK MENINGKATKAN PEMAHAMAN MATERI HAKIKAT DEMOKRASI PANCASILA PADA MATA PELAJARAN PKn SISWA KELAS X-4 SMA NEGERI 1 PADALARANG TAHUN PELAJARAN 2011-2012 - Saepudin, Asep Deta (PEDAGOGIA, 2017)
This research focuses on improving the understanding of material nature effort Pancasila democracy on the subjects of Citizenship Education through Learning Technology (Demonstrate). The problems of this study include: (1) how concrete actions in improving understanding of the nature of matter in the eyes of Pancasila democracy lesson Citizenship Education through Learning Technology (Demonstration) in class X-4 SMAN 1 Padalarang West Bandung Regency 2011-2012 school year? And (2) whether the effort to improve understanding of the nature of the materials on the subjects of Pancasila democracy through technology learning Citizenship Education (Demostrasional) in class X-4 SMAN 1 Padalarang West Bandung Regency 2011-2012 school year to show improvement? Based on data analysis, activity and improved performance of the students obtained data showing that at the meeting with 20 students from the first cycle increased by 54% to 64.75% in the second cycle, the third cycle increased to 72%. Analysis From these data, it can be said that the PBM activities performed quite effective in improving student learning outcomes. The conclusion of this study indicates that the application of the Demonstration method to improve the understanding of the matter: "The essence of Pancasila democracy" in the Subject Civics students of SMAN 1 Padalarang West Bandung Regency 2011-2012 school year has been successful and positive change. significant.